Perilaku Hambatan Panas pada Papan Partisi diperkuat Serat Tandan Kosong Kelapa Sawit - Nursanni, Banu; Siregar, Batumahadi; ., Sutrisno; Wijaya, Kinanti (Fakultas Teknik UMSU, 2023)
The goal of this research was to determine the heat resistance behavior of polymer composite fiber boards with oil palm empty fruit bunches (OPEFB) fillers as influenced by mass density and water absorption, with the hope that partition boards with OPEFB fiber fillers could reduce the heat entering the room from outside vines through directly exposed walls. The partition board under discussion is a heat insulator with a thermal conductivity test impacted by the mass density of the composite. The test method used is ASTM-C-177-2013, which consists of measuring heat propagation by modifying a 40-watt heat source and testing specimens from polymer composite partition boards formed based on standards obtained from partition forming boards with a matrix of polyester resin SHCP 2667 WNC fraction weight with a fiber weight ratio of 25 wt.%, 30 wt.%, and 35 wt.% randomly arranged (chopped strand mat/CSM). The highest thermal conductivity value was observed in a 25 wt.% fiber weight ratio of 0.141 W/m.oC at a void percentage of 7.65% for a 5 minutes test time; 0.146 W/m.oC for a 10 minutes test time; 0.151 W/m.oC for 15 minutes test time at a mass density of 1.16 gr/cm. While the 35 wt.% fiber weight ratio has the lowest thermal conductivity value of 0.137 W/m.oC at a void percentage of 4.24% for a 5 minutes test time; 0.142 W/m.oC for a 10 minutes test time; and 0.147 W/m.oC for a 15 minutes test time at a mass density of 1.24 gr/cm3 and a water absorption capacity of 3.75%. According to the investigation’s findings, the higher the water absorption capacity, the higher the thermal conductivity of the partition board, and the higher the mass density, the lower the thermal conductivity. As a result, the lower the value of the thermal conductivity of the partition board, the better the insulating properties.